Detailed modelling and simulation of different DC motor types for research and educational purposes - Sami, Saif Sabah; Obaid, Zeyad Assi; Muhssin, Mazin T.; Hussain, Ali N. (Institute of Advanced Engineering and Science, 2021)
The devastating impact of Covid-19 pandemic accelerated the shift to e-learning in the higher education. Particularly in the electrical machines courses, that often include laboratory experiments. However, no detailed models of DC motors, developed in MATLAB/Simulink, were reported in literature. Hence, in this paper, a virtual laboratory consist of models of DC motors was built for the first time. The proposed models are easy to use and modify, and allow all machines’ parameters to be altered for students to replicate easily to support and enhance the learning process of electrical machines courses. Consequently, the developed models are effective tools for educational and research purposes. Dynamic models of DC motors were developed using MATLAB/Simulink, namely separately excited, permanent magnet, shunt-connected and series-connected DC motors. Two different approaches for modelling were proposed, the block diagram representation and Simscape based models. The two modelling methods were validated against the built-in DC machine model. The proposed models are easy to use and modify, and allow all machines’ parameters to be altered for monitoring and comparison purposes. Consequently, the developed models are effective tools for research and educational purposes.